Determinan Faktor yang Berhubungan dengan Kejadian Premenstrual Syndrome (PMS) di SMAN 1 Godean, Sleman, D.I. Yogyakarta - Afi Lutfiyati; Masta Hutasoit; Novita Nirmalasari (HEALTHY BEHAVIOR JOURNAL, 2025)
Background: Adolescent reproductive problems will lead to malnutrition, late growth, disease, and stres. During puberty, about 80-90% of woman will experience PMS symptoms. Factors that cause PMS include hormonal factors, genetic factors, lifestyle factors related to weight gain, sleep quality, and physical activity. One of the psychological factors were stress. The symptoms of PMS will be even more intense when the woman continues to experience pressure. Objective: to determine the association between menarche, menstrual cycle, stress level, sleep quality, BMI with the incidence of premenstrual syndrome. Methods: Quantitative research design using a cross-sectional approach. Samples were taken using stratified random sampling technique, namely 99 students of class XI at SMAN 1 Godean. Retrieval of data using google form, namely in July 2020. The research instrument was a questionnaire. The results of the study were analyzed by univariate, bivariate using Somer’s test, and logistic regression for multivariate analysis. Results: In the characterictics of the respondents, most of the female students were at the age of 17 years with a total of 62 students (62.6%), most of the menstrual habits in the routine category were 87 students (87,9%). There were association between sleep quality, stress level with premenstrual syndrome with each value of p=0.001 (OR=7.043; 95%CI=1.542-32.164) and p=0.002 (OR=1.025; 95%CI=0.296-3.554). There was no association between BMI, menstrual cycle, and menarche with the incidence of premenstrual syndrome with p=0.785, p=0.969, p=0.768, respectively. Conclusion: Multivariate test with logistic regression found that the most dominant factors associated with the incidence of premenstrual syndrome were sleep quality.